2021
DOI: 10.3389/fphar.2021.652963
|View full text |Cite
|
Sign up to set email alerts
|

Pyroptosis in the Initiation and Progression of Atherosclerosis

Abstract: Pyroptosis, a newly discovered form of programmed cell death, is characterized by cell swelling, the protrusion of large bubbles from the plasma membrane and cell lysis. This death pathway is mediated by the pore formation of gasdermin D (GSDMD), which is activated by human caspase-1/caspase-4/caspase-5 (or mouse caspase-1/caspase11), and followed with the releasing of both cell contents and proinflammatory cytokines. Pyroptosis was initially found to function as an innate immune effector mechanism to facilita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 91 publications
0
55
0
Order By: Relevance
“…Pyroptosis is also known as inflammatory necrosis of the cell, which is manifested by the continuous expansion of the cell until the cell membrane ruptures and the subsequent release of the cell contents activate a strong inflammatory response [ 41 ]. As an important triggering factor and endogenous regulator of cardiovascular inflammation, pyroptosis not only induces the death of endothelial cells but also leads to enhanced endothelial permeability, promotes the expression of endothelial cell adhesion molecules, recruits monocytes and promotes their differentiation into macrophages, and aggravates blood vessel damage [ 42 44 ]. Studies have shown that pyroptosis regulated by the NLRP3 inflammasome is closely related to the progression of cardiovascular disease [ 43 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis is also known as inflammatory necrosis of the cell, which is manifested by the continuous expansion of the cell until the cell membrane ruptures and the subsequent release of the cell contents activate a strong inflammatory response [ 41 ]. As an important triggering factor and endogenous regulator of cardiovascular inflammation, pyroptosis not only induces the death of endothelial cells but also leads to enhanced endothelial permeability, promotes the expression of endothelial cell adhesion molecules, recruits monocytes and promotes their differentiation into macrophages, and aggravates blood vessel damage [ 42 44 ]. Studies have shown that pyroptosis regulated by the NLRP3 inflammasome is closely related to the progression of cardiovascular disease [ 43 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process can occur anywhere in the body, with different sites leading to different outcomes. In the intrinsic immune cells, NOD-like receptors bind PAMPs or DAMPs ligands that are difficult to be cleared by cellular autophagy (Xiao He et al, 2021), activating the relevant inflammatory bodies and thus contributing to pyroptosis followed by a local or systemic inflammatory response to recruit more intrinsic immune cells to clear the excess PAMPs/DAMPs ligands (Qian et al, 2021). Therefore, as a form of inflammatory cell death, moderate pyroptosis can accelerate the immune response helping to resist pathogenic infections, maintain cellular homeostasis and exert a positive aspect of protecting the organism (Qun .…”
Section: Pyroptosismentioning
confidence: 99%
“…ASC then recruits polymerized pro-caspase-1 through its CARD structural domain (caspase activation and recruitment domain) and induces its own cleavage to form caspase-1 maturation (p10/p20 tetramer). Activated caspase-1 shears inactive IL-1β precursors and IL-18 precursors, converting them into mature inflammatory factors, leading to pyroptosis ( Qian et al, 2021 ). On the other hand, it cleaves GSDMD and oligomerizes the GSDMD-N-terminal fragment, which mediates the formation of membrane pores, resulting in cell swelling and lysis to further promote the release of inflammatory factors and intensify the inflammatory response, inducing pyroptosis ( Winkler and Rösen-Wolff, 2015 ; Liu and Lieberman, 2017 ; Zahid et al, 2019 ).…”
Section: Pyroptosismentioning
confidence: 99%
“…Both cytokines play key roles in atherosclerosis and may participate in modulating VSMCs to a migratory phenotype with enhanced proliferation and expression of inflammatory markers (90)(91)(92). Lastly, NLRP has been linked to gasderminD-dependent pyroptosis in VSMCs, which occurs ubiquitously in atherosclerotic lesions and is a form of cell death that impacts atherogenesis, inflammation, and plaque instability (93).…”
Section: Macrophage To Vsmc Signalingmentioning
confidence: 99%